KARAKTERISTIK HEMATOLOGI BURUNG GOSONG KELAM (Megapodius freycinet) DI PULAU MANSINAM MANOKWARI - Tethool, Angelina N.; Kayadoe, Martha; Koibur, Johan (Fakultas Peternakan Universitas Papua, 2009)
Decreasing population of Gosong Kelam birds (Megapodius freycinet) can be limited by using captivity. Characteristic of haematology were indicator to know about health and physiology satus of animals in a captivity. The aim of the research was to know haematology information of Gosong Kelam birds (Megapodius freycinet) in Mansinam island. The results show that average haematologies value of Gosong Kelam birds were not different to other research results. The number of erythrocyte 2.6x103/mm3, hemoglobin 15.8 gr%, leukocyte 15.9x103/mm3. More over types of leukocyte which are consist of basophils with 3.25% without eosinophils, heterophils 23.5%, lymphocytes 61.75% and monocytes 13%.